Plasma and milk oxytetracycline levels in post parturient sows - Schoneweis, D.; Hummels, S.; Schulteis, L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Plasma and milk samples were collected from three sows injected with LA 200 at 4 hours after injection and at 24-hour intervals thereafter. The single dose was calculated at 1 ml/22 pounds.
Keywords: Swine; Plasma; Milk oxytetracycline; Post parturient sows